Revitalisasi Permainan Tradisional dalam Mengenalkan Nilai-Nilai Kearifan Lokal-Religius pada Anak - Bagus Mahardika; Nihwan; Anas Rangga Buana (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2021)
This study aims to explore information about the revitalization of traditional games in introducing the religious-local wisdom values to children. The method used is a literature review with sources from traditional game studies. Playing for children is a valuable activity, because by playing that they will learn many things, especially traditional games that have many benefits and values that are superior. In this study, the researcher concluded that children who are active in their childhood playing traditional games have skills and agility in language and are good at socializing.